Theoretical and experimental modal analysis of a beam-tendon system. (1st October 2019) - Ondra, V.; Titurus, B.
Highlights: A system consisting of the Euler-Bernoulli beam subjected to tendon-induced axial loading is studied. The system is modelled using a set of partial differential equations derived by Hamilton's principle. The model is thoroughly experimentally validated for a wide range of loadings and configurations. The effect of the tendon tension and its mass on the modal properties and frequency loci veering are studied. Further numerical studies show the effect of the tendon on the torsional modes and structural stability. Abstract: Theoretical and experimental modal analysis of the system consisting of the Euler-Bernoulli beam axially loaded by a tendon is studied in the paper. The beam-tendon system is modelled using a set of partial differential equations derived by Hamilton's principle and the coupling between the beam and the tendon is ensured by the boundary conditions. Theoretical modal analysis is conducted using a boundary value problem solver and the results are thoroughly experimentally validated using a bench-top experiment. In particular, the effect of the tendon tension on the modal properties of the system is studied. It is found that by increasing the tension, the natural frequencies of the beam decrease while the natural frequencies of the tendon increase. It is also shown that these two sets of modes interact with each other through frequency loci veering. The effect of the tendon mass is also experimentally and numerically studied and it is shown that lighter tendon produces fewer vibration modes in the studied frequency region. Two further numerical studies are conducted to demonstrate the effect of the tendon on the torsional modes of the beam, and to study the structural stability. Overall, an excellent agreement between the numerical and experimental results is obtained, giving the confidence in the derived theoretical model.